The phenomenon of dollarization in developing countries’ monetary systems (Economic and Political Thought, 2015)
The lack of reliable domestic financial instruments, including a stable currency,results in domestic entities’ desire, and sometimes a need, to possessmonetary resources from other currency areas. The phenomenon is calleddollarization although it may relate to any currency, including mainly globalcurrencies. The need for dollarization also appears in connection with thenecessity of possessing reserves by the banking system. Official reserves madeof world currencies that are kept by developing countries are definitely higherthan required as standard traditional precautionary measures. It results fromthe lack of the international financial system solutions that might guaranteestable conditions for the functioning of developing economies, which makesthem maintain high monetary reserves. Thus, it seems that dollarization ofdeveloping countries should be treated as an important factor shaping demandfor world money. The specific share of the countries that are world currenciesissuers, including first of all the dollar, in raising demand for world money thatlets them solve their domestic problems is an issue that requires further analysis.On the other hand, the sources of these problems should be looked for inpersistent defectiveness of neoliberal policy of the contemporary capitalism.